The favoured cluster structures of model glass formers - Doye, J; Wales, D; Zetterling, F; Dzugutov, M (2002)
We examine the favoured cluster structures for two new potentials, which both behave as monatomic model glass-formers in bulk. We find that the oscillations in the interatomic potential lead to global minima that are non-compact arrangements of linked 13-atom icosahedra. We find that the structural properties of the clusters correlate with the glass-forming propensities of the potentials, and with the fragilities of the corresponding supercooled liquids.